Gold as Safe Haven Strategy During Covid-19 Pandemic: The Case of Bursa Malaysia - Norasikin Salikin; Norailis Ab. Wahab (Universitas Darussalam Gontor, 2024)
Studies on the property of gold investment as safe haven strategies have been done worldwide. However, the study on the impact of Covid-19 crisis is limited as the crisis is still new. This study is trying to fill in the gap by identifying the safe haven property of gold in Malaysia market. Preliminary results show that performance of gold price is parallel with the performance of KLSE during the pandemic. It shows that the property does not exist in Malaysian market. However, statistical test needs to be done to identify the result precisely. It hopes that result of the study could help investors in constructing better portfolio in managing the risk of their investment